The Effect Of Dried Leaves Nutrient Ingredients Banana Watermelon Plant Growth On Alluvial Soil - Mariana, Mariana; Listiawati, Agustina; Maulidi, Maulidi (Jurnal Sains Pertanian Equator, 2017)
This study aims to determine dried leaves nutrient ingredients banana the best of the watermelon plant growth on alluvial soil. research conducted in the faculty of agriculture universities Tanjungpura pontianak. This study took place from 28 February 2016 to 24 June 2016, using a randomized block design (RAK) consists of a single factor, five treatments and repeated four times with three plant samples. The carrying out of this research are k1=7,5 kg / plot equivalent to 10 ton/ha, k2= 15 kg/ plot eguivalent to 20 ton/ha, k3= 22,5 kg/plot equivalent to 30 ton/ha, k4=30 kg/plot equivalent to 40 to/ha, k5= 37,5 kg/plot equivalent to 50 ton/ha. variable observation in this study was the time of flowering, root volume and dry weight of plants. Award dried leaves nutrient ingredients banana 7,5 kg /seedbed par with 10 ton/ha, an effective dose of the watermelon plant growth on alluvial soil.